Professional sporting events increase seasonal influenza mortality in US cities - Cardazzi, A.; Humphreys, B.; Ruseski, J. E.; Soebbing, B. P.; Watanabe, N. (Economics Faculty Working Papers Series, 6-2020, 2020)
The COVID-19 pandemic shut down sporting events worldwide. Local policy makers and league officials face important decisions about restarting play, especially inprofessional leagues that draw large numbers of spectators to games. We analyze the impact of professional sporting events on local seasonal influenza mortality to developevidence that will help inform sports league reopening policy decisions. Results from adifference-in-differences model applied to data from a sample of US cities that gainednew professional sports teams over the period 1962-2016 show that the presence of games in these cities increased local influenza mortality by between 4% and 24%, depending on sport, relative to cities with no professional sports teams and relative to mortality in those cities before a new team arrived. Influenza mortality fell in citieswith teams in some years when work stoppages occurred in sports leagues. Sports league reopening policies should take into account the role played by sporting eventsin increasing local seasonal flu mortality.